Loss of CRMP2 O-GlcNAcylation leads to reduced novel object recognition performance in mice. Issue 11 (27th November 2019) - Muha, Villo; Williamson, Ritchie; Hills, Rachel; McNeilly, Alison D.; McWilliams, Thomas G.; Alonso, Jana; Schimpl, Marianne; Leney, Aneika C.; Heck, Albert J. R.; Sutherland, Calum; Read, Kevin D.; McCrimmon, Rory J.; et al.
Abstract : Abstract : O-GlcNAcylation is an abundant post-translational modification in the nervous system, linked to both neurodevelopmental and neurodegenerative disease. However, the mechanistic links between these phenotypes and site-specific O-GlcNAcylation remain largely unexplored. Here, we show that Ser517 O-GlcNAcylation of the microtubule-binding protein Collapsin Response Mediator Protein-2 (CRMP2) increases with age. By generating and characterizing a Crmp2 S517A knock-in mouse model, we demonstrate that loss of O-GlcNAcylation leads to a small decrease in body weight and mild memory impairment, suggesting that Ser517 O-GlcNAcylation has a small but detectable impact on mouse physiology and cognitive function.